SUPLEMENTASI INULIN TERHADAP KELANGSUNGAN HIDUP, HEMATOLOGI DAN TOTAL BAKTERI ASAM LAKTAT PADA USUS IKAN LELE SANGKURIANG (Clarias gariepinus) - Situmeang, Vina Josephine; Agustina, Agustina; Nikhlani, Andi (Program Studi Budidaya Perairan, Fakultas Pertanian, Universitas Sriwijaya, 2023)
This study aims to evaluate the effect of inulin in feed with different doses on survival rates, hematological parameters and the number of lactic acid bacteria in the gut of sangkuriang catfish (Clarias gariepinus). This study used a completely randomized design (CRD) with 4 treatments 3 replications with inulin doses: P0 0 g/kg feed; P1 1.5 g/kg feed, P3 3 g/kg feed, and P4 6 g/kg feed. Fish reared in plastic container with a volume of 40 L of water for 30 days. Feeding according to treatment was carried out three times a day in the morning, afternoon and evening using the at satiation method. The results showed that administration of inulin did not significantly affect the survival rate of fish, hemoglobin levels, hematocrit and total erythrocytes (P>0.05), but significantly affected total leukocytes and the number of lactic acid bacteria in catfish gut (P<0.05). The survival rate of sangkuriang catfish ranged from 88.89-97.78%, and the highest leukocyte count was at P2 of 12.86 x 104 cells/mm3 compared to other treatments. The number of lactic acid bacteria in the range of 7.12-8.22 x104 CFU/mL in the inulin treatment while the control was 1.97 x104 CFU/mL. Based on these results, inulin has the potential as a prebiotic in sangkuriang catfish culture.